Romantic Partner Alcohol Misuse Interacts With GABRA2 Genotype to Predict Frequency of Drunkenness in Young Adulthood - Gajos, Jamie M. (Journal of contemporary criminal justice, 2019)
Previous research has identified the importance of romantic partners—including spouses, significant others, and dating partners—for influencing the engagement in health-risking behaviors, such as alcohol misuse during emerging adulthood. Although genetic factors are known to play a role in the development of young adult alcohol misuse, little research has examined whether genetic factors affect young adults’ susceptibility to their romantic partners’ alcohol misusing behaviors. The current study tests whether a single nucleotide polymorphism in the GABRA2 gene (rs279845) moderates the relationship between romantic partner alcohol misuse and frequency of drunkenness in young adulthood. Results revealed differential risk associated with romantic partner alcohol misuse and young adult drunk behavior according to GABRA2 genotype, such that individuals with the TT genotype displayed an elevated risk for frequency of drunkenness when romantic partner alcohol misuse was also high (incidence rate ratio = 1.06, p ⩽ .05). The findings demonstrate the potential for genetic factors to moderate the influence of romantic partners’ alcohol misuse on drunk behavior during the transition to young adulthood.